2020
DOI: 10.1016/j.jacep.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmias and COVID-19

Abstract: Current understanding of the impact of coronavirus disease-2019 (COVID-19) on arrhythmias continues to evolve as new data emerge. Cardiac arrhythmias are more common in critically ill COVID-19 patients. The potential mechanisms that could result in arrhythmogenesis among COVID-19 patients include hypoxia caused by direct viral tissue involvement of lungs, myocarditis, abnormal host immune response, myocardial ischemia, myocardial strain, electrolyte derangements, intravascular volume imbalances, and drug sides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(192 citation statements)
references
References 76 publications
(86 reference statements)
2
156
0
6
Order By: Relevance
“…Studies also reported an increased incidence of VT/VF in patients with elevated troponin, suggesting the development of arrhythmias may be a result of MI [ 89 ]. The incidence of arrhythmia in COVID-19 may be in the setting of respiratory distress, myocarditis, electrolyte derangements, intravascular volume imbalance, or drug side effects, as reviewed by Dherange et al [ 94 ]. However, the mechanisms resulting in their development remain to be elucidated.…”
Section: Cardiovascular Complications In Covid-19mentioning
confidence: 99%
“…Studies also reported an increased incidence of VT/VF in patients with elevated troponin, suggesting the development of arrhythmias may be a result of MI [ 89 ]. The incidence of arrhythmia in COVID-19 may be in the setting of respiratory distress, myocarditis, electrolyte derangements, intravascular volume imbalance, or drug side effects, as reviewed by Dherange et al [ 94 ]. However, the mechanisms resulting in their development remain to be elucidated.…”
Section: Cardiovascular Complications In Covid-19mentioning
confidence: 99%
“…In the report by Colon et al, 19 out of 119 (16.5%) patients, all admitted in ICU, developed new-onset atrial arrhythmias, including atrial fibrillation (63%), atrial flutter (32%) and atrial tachycardia (5%) [ 62 ]. Atrioventricular/ventricular block and QT prolongation have been reported in association with SARS-CoV-2 infection, with incidence of 11.8% and 13% respectively [ 60 ].…”
Section: Arrhythmias and Sudden Cardiac Arrest: Role Of Advanced Imagmentioning
confidence: 99%
“…Critically ill patients were more likely to experience arrhythmia at a strikingly high incidence of 44% [56]. The exact cause of the increase of cardiac injury and arrhythmias is unclear, but is currently believed to be most likely secondary to systemic effects and possibly from drug side effects [58,59]. There is growing evidence to suggest COVID-19 may directly affect the heart as well.…”
Section: The Direct and Indirect Cardiac Effects Of The Covid-19 Virusmentioning
confidence: 99%
“…There is growing evidence to suggest COVID-19 may directly affect the heart as well. Atrial and ventricular arrhythmias have been associated with fulminant myocarditis and cardiogenic shock in COVID-19 patients [59][60][61]. A recent study of 100 recovering patients~70 days post COVID-19 diagnosis demonstrated that 78% of patients had cardiac involvement on MRI of which 60% had signs of ongoing inflammation [62•].…”
Section: The Direct and Indirect Cardiac Effects Of The Covid-19 Virusmentioning
confidence: 99%